TRACEABILITY, VETERINARY PUBLIC HEALTH AND FOOD SECURITY: AN INTEGRAL APPROACH - Cartín-Rojas, Andrés (2013)
The traceability of animals and animal products throughout the production process allows identifying, verifying and isolating potentially harmful foods for consumers, while ensuring the control of animal diseases of mandatory reporting, facilitating control of zoonotic diseases and allowing access to specific and more profitable markets. Traceability and animal identification programmes will be strengthened in the next few years as a system of quality assurance in which veterinary services will have a key role in the implementation, monitoring and evaluation for the proper functioning of public health worldwide.